A STUDY ON ALLICIN AS BIOINHIBITOR OF UREA HYDROLYSIS FOR UREA FERTILIZER EFFICIENCY - MATHIALAGAN, RANITHA (2021)
Potency of allicin to inhibit urease, natural enzyme in soil that catalyzes urea hydrolyzation, is well documented and being commercially practiced in medicinal however in agriculture its compatibility still remains enigmatic. Therefore, in this study the reduction of rapid hydrolyzation on applied urea was attempted in soil through the addition of allicin as urease inhibitor. Soil amended with different allicin concentration was tested for its inhibitory effect on soil urease. This is followed by evaluation on kinetic and inhibitory properties in which effect of allicin at various substrate concentration (S) and enzyme concentration (E) be analyzed. Next, the compatibility of palm stearin as adhesive for allicin potential powder (APP) in urea coating was examined.